2022
DOI: 10.1186/s12882-022-02666-1
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular mass regression, all-cause and cardiovascular mortality in chronic kidney disease: a meta-analysis

Abstract: Background Cardiovascular disease is an important driver of the increased mortality associated with chronic kidney disease (CKD). Higher left ventricular mass (LVM) predicts increased risk of adverse cardiovascular outcomes and total mortality, but previous reviews have shown no clear association between intervention-induced LVM change and all-cause or cardiovascular mortality in CKD. Methods The primary objective of this meta-analysis was to inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…In the latest meta-analysis by Maki et al, it was shown that LVM change may be useful as a surrogate marker the for benefits of interventions intended to reduce mortality risk in CKD [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the latest meta-analysis by Maki et al, it was shown that LVM change may be useful as a surrogate marker the for benefits of interventions intended to reduce mortality risk in CKD [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of LVH is an independent predictor of mortality across the CKD spectrum and interventions that induce reductions in LV mass (e.g. exercise programmes, extended dialysis regimens, anaemia control) are associated with significant reductions in the risk of all-cause mortality in patients with CKD 45 . The causes of LVH in CKD are multi-factorial and include factors related to afterload, factors related to preload and non-haemodynamic factors 46 .…”
Section: [H1] Cardiovascular Healthmentioning
confidence: 99%
“…Second, the follow‐up time of 12 months failed to assess differences in patient outcomes, and there was some uncertainty in using surrogate LVMI as the primary outcome indicator. However, the results of the most recent meta‐analysis suggest that interventions to reduce LVM are associated with a significant reduction in the combined risk of ACM; hence, LVM is a good surrogate indicator [41].…”
Section: Discussionmentioning
confidence: 99%